Digital Readiness and Extension Support in Chili Farmers' Plantix Adoption for Pest Control in Indonesia - Putri Aulia Wardani; Gunawan Gunawan; Arum Pratiwi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Digital transformation in agriculture has encouraged the development of artificial intelligence-based applications such as Plantix, which assists farmers in diagnosing plant pests and diseases through image analysis. Although Plantix has proven technically effective, its adoption rate among Indonesian farmers remains low and is presumably influenced by internal and external factors that have not been widely studied at the local level. This study aims to analyze the factors influencing chili farmers' adoption of the Plantix application in Kayukebek Village, Indonesia. A quantitative approach was used with 58 respondents selected through purposive sampling from a population of 188 chili farmers. Data were analyzed using multiple linear regression with two independent variables: farmer characteristics (age, education, farming experience, smartphone use frequency) and environmental support and interaction (extension support, access to information and training, social influence, internet access). The results show that the regression model explains 45.5% of the variation in Plantix adoption (R² = 0.455) and is significant simultaneously (F = 5.118; p < 0.001). Partially, smartphone use frequency, agricultural extension support, and social and environmental influence significantly affect adoption (p < 0.05), while age, education, farming experience, information/training access, and internet access do not. These findings indicate that adoption is driven more by digital readiness, extension assistance, and peer influence than by farmers' demographic characteristics or the availability of infrastructure alone, and provide a basis for designing more targeted extension strategies. Contribution to Sustainable Development Goals (SDGs): SDG 1: No PovertySDG 2: Zero HungerSDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production